The Position of Non-Disclosure and Confidentiality Agreement, in Protecting Patient Privacy at a Beauty Clinic - Cokorda Gede Swetasoma (Faculty of Law, Universitas Pekalongan, 2025)
Services at beauty clinics are carried out by the professionals with expertise in the field of medical skin care and beauty. In order to promote the products and services provided, these clinics carry out promotions both through social and electronic media. Therefore, it is possible that the beauty clinics will display photos or videos of patients for promotion. This will be a problem related to the law if the patient himself does not want his information to be used in promotional tools. There are even health workers at a beauty clinic who publish the public figure without permission. In this study, professional ethics will be discussed as the basis for protecting patient privacy, the Non-disclosure Agreement and Confidentiality Agreement in the Indonesian Civil Code as well as the Non-disclosure Agreement and Confidentiality Agreement to Maintain the Confidentiality of Patient Information. Professional ethics is actually the basis for protecting patient privacy. Patient confidentiality is a part of company confidentiality where the company can make a non-disclosure agreement that applies to clinic workers and partners of the beauty clinics. Confidentiality regulated in the confidentiality agreement does not only relate to the company's trade secrets but includes the confidentiality of patient information which is part of patient privacy information